الرواية الجزائرية المعاصرة (التحولات والبحث عن شكل) - مشري, بن خليفة; عمري, الطاهر (جامعة الوادي - university of Eloued, 2020)
يمكننا اختزال المشهد الروائي في الجزائر في اتجاهين كبيرين، الأول حداثي والثاني ما بعد حداثي، أما الاتجاه الأول فهو الاتجاه التجريبي في الرواية الجزائرية، ويمثل هذا التحول في السرد الجزائري تيار التجريب بضرورة تجاوز الأنماط السائدة إلى أنماط جديدة في محاولة للمغامرة إن على مستوى تنظيم عملية السرد أو الأسلوب اللذين صاغهما كتاب كبار، والاتجاه الثاني فهو اتجاه الجيل الجديد أو ما يعرف بروايات الجيل الجديد، وهو اتجاه ما بعد حداثي، وتسعى هذه الدراسة إلى الوقوف على الجهود الكثيرة التي تبناها هؤلاء الكتاب من أجل إيجاد الشكل المناسب للرواية لتطوير التقنيات السردية. كلمات مفتاحية: الرواية، معاصرة، تحولات، السرد، شكل. Abstract: We can reduce the narrative scene in Algeria in to big directions, the first is modern and the second is post-modern. The first one is the empirical trend in the Algerian novel, this shift in the Algerian narratives represents the current trend of experimentation with the need to transcend the prevailing patterns to new patterns in an attempt to adventure, at the level of organizing the narration or style developed by writers such The second on is the trend of the new generation or what is known as the novels of the new generation, which is a post-modern trend This study examines the many efforts that these authors have taken to find the appropriate form of the novel to develop narrative techniques .
The contemporary Algerian novel (transformations and the search for form)
مقال
Keywords: Contemporary, novel, transformations, narration, form; الرواية، معاصرة، تحولات، السرد، شكل